Tantrasamuccaya of Nārāyaṇa : with the commentaries Vimarśinī of Śaṅkara and Vivaraṇa of Nārāyanaśisya ; reprinted with an English translation of the text - Nārāyaṇa (New Bharatiya Book Corporation, 2014)
Compendium for Tantric rituals and rules for temple architecture and sculpture; text with Sanskrit commentaries and English translation.